Recipient Adipose-Derived Stem Cells Enhance Recipient Cell Engraftment and Prolong Allotransplant Survival in a Miniature Swine Hind-Limb Model. Issue 8 (August 2017) - Kuo, Yur-Ren; Chen, Chien-Chang; Chen, Yen-Chou; Chien, Ching-Ming
Donor mesenchymal stem cells (MSCs) could prolong vascularized composite allotransplantation (VCA) survival in our previous studies. However, recipient adipose tissue is easier to harvest than donor tissue for preconditioning modulation. Hence, this study investigated the efficacy of recipient autologous adipose-derived stem cells (rADSCs) for VCA survival. The heterotopic hind-limb transplantation from female donor to male recipient was performed in outbred miniature swine. Group I ( n = 6) was untreated controls. Group II ( n = 4) obtained rADSCs infusions (given on weeks 0, +1, +2, and +3). Group III ( n = 4) obtained tacrolimus (FK506, weeks 0 to +4). Group IV ( n = 8) received irradiation (IR; day −1), FK506 (weeks 0 to +4), and rADSC infusions (weeks 0, +1, +2, and +3). The results revealed treatment with multiple injections of rADSCs along with IR and FK506 resulted in a statistically significant increase in allograft survival. The percentage of CD4 + /CD25 + /Foxp3 + regulatory T cells were significantly increased in the rADSC-IR-FK506 group as compared to controls. Analysis of recipient peripheral blood revealed that transforming growth factor β1 (TGFβ1) was significantly increased in the rADSC-IR-FK506 group. The polymerase chain reaction (PCR) analysis and immunohistochemical staining showed recipient sex-determining region of Y (SRY) chromosome gene expression existed in donor allotissues in the rADSC-IR-FK506 group. These results indicate that rADSCs in addition to IR and transient immunosuppressant could prolong allotransplant survival, modulate T-cell regulation, and enhance recipient cell engraftment into the allotransplant tissues.